Encourage the Creation and Development of Handicraft Brands in Students at the Social Foundation, Tambun, West Java - Hardini, Resti; Melati, Melati; Elwisam, Elwisam; Putra, Suadi Sapta; Saharso, Saharso; Nur, Muhammad (Ruang Cendekia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity aims to improve the skills of high school students at the Tambun Social Foundation in making and developing brands for the handicraft products they produce. These high school students are students who are accommodated in foundations that accommodate orphans and the poor with all their limitations. This training was provided in response to the need to expand their knowledge and abilities in aspects of product marketing, especially in terms of effective branding and efforts to establish independence in improving welfare. The methods used in this training include lectures, group discussions and direct practice. Apart from that, a questionnaire was given about understanding branding before and after the activity was carried out. Before the implementation of PKM, only 20% of participants understood branding in product marketing activities. After carrying out socialization and training activities, 80% of participants understood the branding strategy for the handicraft products produced. The results of this activity showed an increase in students' understanding of the importance of brands in marketing strategies and their ability to create and develop brands that are attractive and in accordance with product characteristics. they. It is hoped that the impact of this training will be to increase the competitiveness of handicraft products made by students in local and wider markets as well as to form independence and improve welfare.